2002
DOI: 10.1159/000048228
|View full text |Cite
|
Sign up to set email alerts
|

Increased Response of Plasma Allopregnanolone to Corticotropin-Releasing Hormone in Obese Patients

Abstract: Allopregnanolone is a neuroactive steroid present in the brain, but also measurable in systemic circulation. It exhibits anxiolytic and anticonvulsant effects and is able to produce hyperphagia. Since eating behavior disturbances and increased peripheral basal sympathetic activity have been reported in obese subjects, the present study investigated allopregnanolone and catecholamine (epinephrine and norepinephrine) responses to corticotropin-releasing hormone (CRH) in obese subjects. Blood was sampled from 39 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Moreover, for the entire sample of women, higher luteal phase allopregnanolone tended to be associated with lower luteal phase cortisol concentrations (r=−0.32, P=0.05). Although it should be pointed out that higher allopregnanolone concentrations in obese subjects in response to a CRF challenge test was not found to be related to plasma cortisol concentrations (Menozzi et al, 2002).…”
Section: Hpa Axis and Gaba A Receptor Function In Pmddmentioning
confidence: 86%
See 1 more Smart Citation
“…Moreover, for the entire sample of women, higher luteal phase allopregnanolone tended to be associated with lower luteal phase cortisol concentrations (r=−0.32, P=0.05). Although it should be pointed out that higher allopregnanolone concentrations in obese subjects in response to a CRF challenge test was not found to be related to plasma cortisol concentrations (Menozzi et al, 2002).…”
Section: Hpa Axis and Gaba A Receptor Function In Pmddmentioning
confidence: 86%
“…Suppression of adrenal steroidogenesis with dexamethasone markedly reduced allopregnanolone, indicating that in humans both ovary and adrenal cortex are major sources of circulating allopregnanolone. Subsequent work by this group has yielded a similar time course to peak plasma allopregnanolone response to the endocrine CRF challenge in healthy male and female controls, although not in women with hypothalamic amenorrhea who fail to show any increase in allopregnanolone (Meczekalski et al, 2000) or in obese men and women who show an exaggerated allopregnanolone response to CRF infusions with an earlier peak (Menozzi et al, 2002). Taken together, the results of these endocrine challenge studies suggest that neuroactive steroids may increase in response to stress in healthy humans as they do in animals.…”
Section: Stress Dysregulation In Neuroactive Steroids: Implications Fmentioning
confidence: 91%
“…The relationship between adrenal secretion and obesity remains unclear, as increased basal cortisol secretion was also reported in obese subjects. 42,43 Although a single morning measurement of serum cortisol (such as all the other hormones with a known circadian rhythm) is not representative of the circadian activity of the HPA axis, the finding of normal morning cortisol levels suggests that changes in DHEAS in our pubertal obese girls were not owing to an overactive CRH/ACTH system, prompting a dissociation in the adrenal secretion of DHEAS and cortisol.…”
mentioning
confidence: 93%
“…In contrast to this hypothesis, a few small studies have demonstrated higher allopregnanolone levels in women with AN vs healthy controls (Galderisi et al, 2003;Monteleone et al, 2001). Studies of neuroactive steroids in obesity are limited; two studies, one in women alone and one in both sexes combined, reported higher levels of allopregnanolone in obese than normal-weight individuals without consideration of comorbid psychiatric symptomatology (Menozzi et al, 2002;Monteleone et al, 2003). However, all these studies were limited by the use of immunoassays to measure allopregnanolone levels, which are particularly vulnerable to cross-reactivity with similarly structured steroid hormone metabolites (Cheney et al, 1995a;Siekmann, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…However, all these studies were limited by the use of immunoassays to measure allopregnanolone levels, which are particularly vulnerable to cross-reactivity with similarly structured steroid hormone metabolites (Cheney et al, 1995a;Siekmann, 1979). Additionally, while some studies exclude women on oral contraceptives (Monteleone et al, 2001;Monteleone et al, 2003) and control for the follicular phase of the menstrual cycle (Menozzi et al, 2002;Monteleone et al, 2001;Monteleone et al, 2003), others (Galderisi et al, 2003) do not specify these conditions, which are critical in the assessment of neuroactive steroids.…”
Section: Introductionmentioning
confidence: 99%